Restaurant Diners’ Switching Behavior During the COVID-19 Pandemic: Protection Motivation Theory - Mahmood, Hamid; Rehman, Asad Ur; Sabir, Irfan; Rauf, Abdul; Afthanorhan, Asyraf; Nawal, Ayesha (Frontiers in Psychology, 2022)
The unsettling fear of COVID-19 infections has caused a new trend in consumer behavior in the food and beverage industry. The unprecedented COVID-19 pandemic has shifted consumers' preferences from eat-in to online delivery. This research aims to measure the impact of consumers' motivation to protect themselves from contracting COVID-19, which explains why people switch from eat-in to online food delivery. We adopted the Theory of Protection Motivation (PMT) to explain consumer switching behavior during the COVID-19 pandemic. The present study investigated the mediating effect of switching intention on the relationship between Vulnerability, Altruistic Fear, Anticipated Regret, and Switching Behavior. Simultaneously, we examined the role of Brand Awareness as a moderator of behavioral choices of consumers switching from eat-in to online delivery. We collected data from 681 eatery consumers in Kuala Terengganu, Malaysia, using scenario-based survey questionnaires (327 eat-in respondents and 354 online delivery respondents). Then, the data were analyzed using Structural Equation Modeling (SEM). This new generation analysis was conducted using the Analysis of Moment Structure (AMOS) (v.24.0) and the Statistical Package for Social Science (SPSS – version 25.0). The Results indicated that consumer vulnerability, altruistic fear, and anticipated regret of COVID-19 increased consumers' propensity to shift from eat-in to online food delivery. Allegedly, consumer behavioral control and intention of switching toward online delivery, pointedly affected by switching behavior. The results indicated that consumer vulnerability, altruistic fear, and anticipated regret of COVID-19 increased the shifting of restaurant dine-in patterns and made the intention to switch to online delivery. Consumers' alleged behavioral control and their intention of switching toward online delivery, pointedly affected by switching behavior. We also found that brand awareness moderately affects switching behavior toward restaurant settings. The present research contributes to developing the consumer behavior model of switching from eat-in to online delivery. This study also provides eatery customers and the business community with a safer and healthier proposition of shifting to online food delivery during the pandemic.